Human Relationship Management to Enhance Organizational Performance through Effective Communication and Team Collaboration - Sarimah; Fauziah Hayati Fazrin; Tisatun; Efrita Norman (MES Management Journal, 2024)
The research explores the role of Human Relationship Management (HRM) in enhancing organizational performance through effective communication and team collaboration. This study aims to provide a comprehensive understanding of how structured communication and well-managed collaboration can positively impact productivity and project completion. The methodology used is a Systematic Literature Review (SLR), analyzing relevant studies from 2019 to 2024. The results indicate that structured communication increases organizational productivity by 30%, while effective team collaboration accelerates project completion by 20%. Additionally, HRM implementation can reduce internal conflicts by 15%, contributing to improved efficiency. The major conclusion is that HRM significantly enhances organizational performance by fostering a productive and harmonious work environment. This study contributes to the field by offering practical guidelines for organizations to adopt HRM strategies that emphasize communication and collaboration. The findings also provide a solid theoretical foundation, aligning with established theories on social interaction, team collaboration, and conflict management. The study's limitation lies in its reliance on existing literature from a limited timeframe, suggesting the need for further empirical testing across various organizational contexts.